1987
DOI: 10.1111/j.1365-2494.1987.tb02107.x
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and chemical changes during the first 22 days in Italian ryegrass and cocksfoot silages made in laboratory silos

Abstract: Although many aspects of grass silage have received intensive study, the changes that take place within the grass blades during ensilage have received little attention.In two factorial experiments Itahan ryegrass (cv. Lemtal) and cocksfoot (indigenous) were ensiled in laboratory silos (capacity 0-2 kg) with the grass under pressure (700 Pa) and subjected to two treatments (with or without 3-3 1 f 85% formic acid) and two silos from each treatment opened on eight sampling dates(l,2,3,4,7,10,14 and 21 d).For eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Formic acid application may result in more extensive cell membrane damage and, as a consequence, more extensive lipolysis during the ensilage of grass than that for RC. Formic acid addition is known to disrupt cell structure in grasses (Winters et al, 1987), but there are no reports for forage legumes, including RC.…”
Section: Lipolysis and Proteolysis Influenced By Polyphenol Oxidase Amentioning
confidence: 99%
“…Formic acid application may result in more extensive cell membrane damage and, as a consequence, more extensive lipolysis during the ensilage of grass than that for RC. Formic acid addition is known to disrupt cell structure in grasses (Winters et al, 1987), but there are no reports for forage legumes, including RC.…”
Section: Lipolysis and Proteolysis Influenced By Polyphenol Oxidase Amentioning
confidence: 99%
“…In contrast, no increase in the volume of effluent with enzymes was found by Brolly (1986) with lucerne and Kennedy (1987) with grass silage. Likewise enzyme treatment, FA releases cell sap by penetrating beyond the epicuticular layer into the tissue and by disrupting mesophyll cell membranes (Winters et al 1987). The reaction is beneficial for rapid fermentation but leads to increased effluent formation with high moisture grasses (Pedersen et al 1973; Bastiman 1976).…”
Section: In-silo Lossesmentioning
confidence: 99%
“…However, many authors evaluating silages made from different crops have reported initial populations from 3.7 to 6.3 log CFU g -1 of silage with good conservation of ensilaged forage (Higginbotham et al, 1998;Driehuis et al, 2001;Whiter & Kung Jr., 2001). Considering our data, population size of lactic-acid bacteria at the beginning of ensilage was not enough for an effective production of lactic acid, but from the first day of fermentation, this microorganism population increased enough to promote a fast silage acidification.…”
Section: Microbiologic Profilementioning
confidence: 99%
“…However, during the initial phase of the ensilage process vegetal cell enzymes are capable to disrupt the cell structure to turn the nutrients required for fermentation available (Winters et al, 1987 andChamberlain, 1987). In studies with Italian ryegrass (Lolium multiflorum), after 6-7 days of ensilage an increase of 30% in the soluble carbohydrate level was observed due to ruptures of chemical bonds within structural carbohydrates, mainly hemicellulose (Chamberlain, 1987).…”
Section: Fermentative Profilementioning
confidence: 99%